2017
DOI: 10.3766/jaaa.16115
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implantation in Children with Postlingual Progressive Steeply Sloping High-Frequency Hearing Loss

Abstract: CIs provided benefit for children with steeply sloping bilateral hearing loss for whom hearing aids did not provide adequate auditory access. In our cohort, significant improvements in speech understanding occurred rapidly postactivation. Preservation of residual hearing in children with a traditional CI electrode is possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Modified trajectory, electrode designs and additional oto-protective measures further improved the hearing preservation (HP) results. The technique offers new possibilities to treat children with language and speech deficiencies that are caused by mid-to high-frequency hearing loss during early development with remaining low tone hearing, that benefit little from hearing aid amplification (Carlson et al, 2017;Kuthubutheen et al, 2012;Meredith et al, 2017;Wilson et al, 2016). Despite initial success, it became apparent that long-term studies are necessary to validate conceivable progressive deterioration of residual hearing.…”
Section: Introductionmentioning
confidence: 99%
“…Modified trajectory, electrode designs and additional oto-protective measures further improved the hearing preservation (HP) results. The technique offers new possibilities to treat children with language and speech deficiencies that are caused by mid-to high-frequency hearing loss during early development with remaining low tone hearing, that benefit little from hearing aid amplification (Carlson et al, 2017;Kuthubutheen et al, 2012;Meredith et al, 2017;Wilson et al, 2016). Despite initial success, it became apparent that long-term studies are necessary to validate conceivable progressive deterioration of residual hearing.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that children with PTA poorer than 60 dB HL have a 75% chance of performing better with a CI than a HA [Leigh et al, 2016]. Despite the proven benefits of cochlear implantation in children with residual hearing and poor word recognition [ (Carlson et al 2015); Gratacap et al, 2015;Meredith et al, 2017], the current FDA guidelines are limited to children with, at best, a severe-to-profound hearing loss. With a significant improvement from pre-to postoperative word recognition, our results support previous work indicating benefits of implantation in nontraditional pediatric CI candidates.…”
Section: Discussionmentioning
confidence: 99%
“…They found an average 26 percentage point increase in open-set word recognition after 1 year of CI use. Meredith et al [2017] found a mean word recognition increase of 57 percentage points 1 month after activation in children with high-frequency hearing loss. Carlson et al [2015] called for changes in pediatric candidacy criteria after finding a mean speech recognition improvement of 63 percentage points following cochlear implantation in children with less than severe hearing loss and speech perception skills exceeding 30%.…”
Section: Introductionmentioning
confidence: 89%
“…Preservation of low-frequency hearing resulted in excellent pure tone thresholds and speech perception scores, even in children. 7 Moreover, Todt et al . 8 suggested using the round window route for electrode insertion to preserve vestibular function.…”
Section: Introductionmentioning
confidence: 99%